Salt-resistant drag reducer for oil field fracturing
By using composite polyglutamic acid and by modification of 1-benzyl-3-methyltriazolium chloride and methacrylic acid, an anti-salt drag reducing agent with a stable ion shielding layer is formed, which solves the problem of degradation of traditional drag reducing agents in high-salt environments, and achieves higher drag reducing effect and salt resistance.
Patent Information
- Application Number
- CN202510293756.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In high-speed flow or high-salt environment, the molecular structure of traditional anti-salt drag reducing agents will be affected by salt ions, resulting in salt degradation, flocculation and other phenomena, resulting in a degradation of performance.
The polyglutamic acid is used as the main component, and the polyglutamic acid is grafted and copolymerized by 1-benzyl-3-methyltriazolium chloride salt, and methacrylic acid is added to form an anti-salt drag reducing agent with a stable ion shielding layer.
In a high-salt environment, the molecular chain of composite polyglutamic acid maintains stretchability, reduces intermolecular entanglement and aggregation, optimizes the conformation of the molecular chain, and improves the drag reduction effect and salt resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drag reducers, in particular to a salt-resistant drag reducer for oilfield fracturing. Background Art
[0002] In the field of oil extraction, oilfield fracturing technology is an important means to increase oil and gas production. As exploration and development advances to complex reservoirs such as deep, ultra-deep and marine, the requirements for fracturing technology are also increasing. During fracturing construction, drag reducers, as core components, can significantly reduce the flow resistance of fracturing fluid in pipelines and formations, improve pumping efficiency, and thus ensure the smooth progress of fracturing operations. However, in actual applications, many oil reservoir formation water mineralization is extremely high and contains a large amount of salts (such as sodium chloride, calcium chloride, etc.), which puts higher requirements on the performance of drag reducers.
[0003] At present, the molecular structure of traditional salt-resistant drag reducers will be affected by salt ions in high-speed flow or high-salt environment, resulting in salt precipitation, flocculation and other phenomena, resulting in performance degradation. In view of this, we propose a salt-resistant drag reducer for oilfield fracturing. Summary of the invention
[0004] The purpose of the present invention is to provide a salt-resistant drag reducer for oilfield fracturing, so as to solve the problem in the above background technology that the molecular structure of traditional salt-resistant drag reducers will be affected by salt ions in high-speed flow or high-salt environment, resulting in salting out, flocculation and other phenomena, resulting in performance degradation.
[0005] To achieve the above object, the present invention provides a salt-resistant drag reducer for oilfield fracturing, comprising the following raw materials: 50-70 parts by weight of composite polyglutamic acid, 3-10 parts by weight of polyethyleneimine, 0.5-2 parts by weight of azobisisobutyronitrile, 1-5 parts by weight of hydroxyethyl cellulose, 0.1-0.5 parts by weight of hydroquinone monomethyl ether, and 0.5-2 parts by weight of dodecyl mercaptan; The composite polyglutamic acid is prepared by grafting and copolymerizing polyglutamic acid with 1-benzyl-3-methyltriazolium chloride and adding methacrylic acid.
[0006] Preferably, the preparation method of the composite polyglutamic acid is as follows: S1.1. Weigh the following raw materials in parts by weight respectively: 60-90 parts by weight of polyglutamic acid, 10-30 parts by weight of 1-benzyl-3-methyltriazolium chloride, 20-50 parts by weight of methacrylic acid, 0.5-2 parts by weight of potassium persulfate, 10-20 parts by weight of N,N-dimethylformamide, and 10-20 parts by weight of ethanol; S1.2, adjust the pH value of the polyglutamic acid solution to 8-10 with 0.1-1 mol / L sodium hydroxide, and stir at 300-600 rpm for 15-30 min; place the polyglutamic acid solution in a constant temperature water bath, control the temperature at 40-50°C, and stir for 30-60 min; S1.3, dissolving 1-benzyl-3-methyltriazolium chloride in N,N-dimethylformamide, and adding dropwise to the polyglutamic acid solution. After the addition is completed, stirring at a speed of 400-600 rpm for 2-4 hours to form a polyglutamic acid intermediate with a triazolium salt structure; The triazolium ions in 1-benzyl-3-methyltriazolium chloride have a specific charge distribution and spatial structure, and can form a stable ion shielding layer around the polyglutamic acid molecules through electrostatic shielding. In a high-salt environment, this shielding layer can effectively block the direct action of a large number of salt ions in formation water on the polyglutamic acid molecules, reduce the damage and interference of salt ions on the polyglutamic acid molecular chains, thereby maintaining the good morphology and performance of the polyglutamic acid molecules and improving their salt resistance. In addition, the grafted 1-benzyl-3-methyltriazolium chloride can also change the interaction within the polyglutamic acid molecules, for example, through electrostatic action, hydrogen bonding and other means, it interacts with certain groups on the polyglutamic acid molecular chain, so that the molecular chain is more inclined to maintain an extended state under high-salt conditions, avoids curling or aggregation due to the influence of salt ions, maintains the effective size of the molecular chain in the solution, and thus ensures the stability of the drag reduction performance.
[0007] 1-Benzyl-3-methyltriazolium chloride has certain surface activity. After being grafted to polyglutamic acid, polyglutamic acid can be better adsorbed on the surface of the pipeline or formation in the fracturing fluid to form a uniform and stable lubricating film. This lubricating film can effectively reduce the friction coefficient between the fracturing fluid and the inner wall of the pipeline and the formation rock, reduce flow resistance, improve the pumping efficiency of the fracturing fluid, and make the fracturing operation smoother; at the same time, the rheological properties of the grafted copolymerized polyglutamic acid in the solution are also optimized, so that it maintains a high viscosity at low shear rates, which is conducive to carrying proppants; and at high shear rates, the viscosity can be rapidly reduced to reduce flow resistance. This good rheological property can effectively improve the comprehensive performance of the fracturing fluid.
[0008] S1.4, raising the reaction temperature of the polyglutamic acid intermediate with a triazolium salt structure to 60-70°C, and adding methacrylic acid dropwise at a rate of 0.5-2 mL / min; after the addition is completed, adding potassium persulfate solution, and stirring the reaction at 60-70°C at a speed of 400-600 rpm for 6-10 hours; 1-Benzyl-3-methyltriazolium chloride can interact with the carboxyl groups on the polyglutamic acid molecular chain through its ionic groups, thereby enhancing the negative charge density of the molecular chain and improving the salt resistance. In a high-salt environment, the electrostatic repulsion between the negative charge and the salt ions can effectively resist the compression and destruction of the molecular chain by the salt ions, maintain the stretched state of the molecular chain, and improve the salt resistance. In addition, the addition of methacrylic acid further enhances the negative charge density of the molecular chain, effectively blocks the direct contact between the salt ions and the polyglutamic acid main chain by forming a more complex ion shielding layer, and performs secondary shielding and dispersion on the salt ions that are close to the molecular chain, thereby maintaining stability in high-salinity formation water.
[0009] The introduction of methacrylic acid not only participates in the copolymerization reaction, making the molecular chain structure more diversified and flexible, but also can introduce new segments and functional groups on the polyglutamic acid molecular chain, changing the flexibility and spatial configuration of the molecular chain, which makes the molecular chain easier to stretch and orient in the solution, thereby reducing the internal friction of the fracturing fluid and improving the drag reduction effect; at the same time, the synergistic effect of methacrylic acid and polyglutamic acid modified with 1-benzyl-3-methyltriazolium chloride further improves the surface activity of the salt-resistant drag reducer. This synergistic effect enables the salt-resistant drag reducer to be more fully adsorbed on the surface of the pipeline and formation, forming a denser and smoother lubricating film, significantly reducing the friction coefficient between the fracturing fluid and the solid surface, reducing flow resistance, and improving pumping efficiency.
[0010] S1.5. After the reaction is completed, the reaction solution is placed in ice water to cool and terminate the reaction; ethanol is added to the reaction solution, and the precipitate is collected by filtration; the precipitate is washed with ethanol for 3-5 times to remove unreacted raw materials, by-products and impurities; the precipitate is dried to obtain composite polyglutamic acid.
[0011] Preferably, in S1.2, the polyglutamic acid solution is prepared by dissolving polyglutamic acid in deionized water to obtain a polyglutamic acid solution having a mass percent concentration of 5-15%.
[0012] Preferably, in S1.3, the rate of adding 1-benzyl-3-methyltriazolium chloride is 0.5-2 mL / min.
[0013] Preferably, in S1.4, the mass percentage concentration of the potassium persulfate solution is 0.5-2%.
[0014] Preferably, in S1.5, the drying temperature is 40-60° C. and the drying time is 24-48 hours.
[0015] Preferably, the preparation method of the salt-resistant drag reducer is as follows: S2.1. Weigh the following raw materials in parts by weight respectively: 50-70 parts by weight of composite polyglutamic acid, 3-10 parts by weight of polyethyleneimine, 0.5-2 parts by weight of azobisisobutyronitrile, 1-5 parts by weight of hydroxyethyl cellulose, 0.1-0.5 parts by weight of hydroquinone monomethyl ether, and 0.5-2 parts by weight of dodecyl mercaptan; S2.2, dissolve the composite polyglutamic acid in deionized water, adjust the temperature to 40-50°C, and stir at 300-400rpm for 30-60min; then add the polyethyleneimine solution, and continue stirring at 300-400rpm for 15-30min to form a mixed system; S2.3, the temperature of the mixed system was raised to 60-70 ℃, azobisisobutyronitrile solution was added dropwise; after the addition was completed, the reaction was continued at a speed of 300-400rpm stirring for 2-4h; S2.4, adding the hydroxyethyl cellulose solution to the mixed system in S1.3, continuing to stir at a speed of 400-500 rpm for 1-2 hours; then adding hydroquinone monomethyl ether and dodecyl mercaptan, stirring at a speed of 200-300 rpm for 15-45 minutes; S2.5. After the reaction is completed, the reaction product is naturally cooled to room temperature and filtered to obtain a salt-resistant drag reducer for oil field fracturing.
[0016] Preferably, in S2.2, the polyethyleneimine solution is prepared by dissolving polyethyleneimine in deionized water to obtain a polyethyleneimine solution having a mass percent concentration of 5-10%.
[0017] Preferably, in S2.3, the azobisisobutyronitrile solution is prepared by dissolving azobisisobutyronitrile in anhydrous ethanol to obtain an azobisisobutyronitrile solution having a mass percentage concentration of 0.1-2%, and the dripping speed is 0.5-2 mL / min.
[0018] Preferably, in S2.4, the hydroxyethyl cellulose solution is prepared by dissolving hydroxyethyl cellulose in deionized water to obtain a hydroxyethyl cellulose solution having a mass percent concentration of 0.5-1%.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. 1-benzyl-3-methyltriazolium chloride is added to the anti-salt drag reducer for oilfield fracturing. Since the triazolium cation in its molecular structure has stable chemical properties, it can enhance the electrostatic repulsion of the polyglutamic acid molecular chain through the ion shielding effect, thereby improving the salt resistance. This effect enables the anti-salt drag reducer to maintain the stretchability of the molecular chain in a high-salt environment, reduce the entanglement and aggregation between molecules, optimize the molecular chain conformation, and improve the drag reduction effect. In addition, the stable triazolium structure of the compound also enhances the chemical stability of polyglutamic acid, making it show higher tolerance in a complex chemical environment and reducing the occurrence of adverse reactions.
[0020] 2. Methyl acrylic acid is added to the anti-salt drag reducer for oilfield fracturing. Since the carboxyl group in the methacrylic acid molecule can ionize a negative charge, it can synergize with other components in the system to effectively resist the interference of salt ions and enhance the salt resistance. At the same time, the double bonds of methacrylic acid can participate in the copolymerization reaction, optimize the molecular chain structure, make the molecular chain more flexible and easy to stretch, thereby reducing the internal friction and improving the drag reduction effect. In addition, methacrylic acid can also adjust the rheological properties of the fracturing fluid and accurately control the viscosity at different shear rates to meet the needs of fracturing construction. It can also react with the cross-linking agent to form a network structure, enhance the gelling performance and scouring resistance, thereby further improving the fracturing effect. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] The invention provides a salt-resistant drag reducer for oilfield fracturing, comprising the following raw materials: 50-70 parts by weight of composite polyglutamic acid, 3-10 parts by weight of polyethyleneimine, 0.5-2 parts by weight of azobisisobutyronitrile, 1-5 parts by weight of hydroxyethyl cellulose, 0.1-0.5 parts by weight of hydroquinone monomethyl ether, and 0.5-2 parts by weight of dodecyl mercaptan; The composite polyglutamic acid is prepared by grafting and copolymerizing polyglutamic acid with 1-benzyl-3-methyltriazolium chloride and adding methacrylic acid.
[0023] Embodiment 1: A salt-resistant drag reducer for oilfield fracturing, comprising the following steps: S2.1. Weigh the following raw materials in parts by weight respectively: 60 parts by weight of composite polyglutamic acid, 6 parts by weight of polyethyleneimine, 1.2 parts by weight of azobisisobutyronitrile, 3 parts by weight of hydroxyethyl cellulose, 0.3 parts by weight of hydroquinone monomethyl ether, and 1.2 parts by weight of dodecyl mercaptan; S2.2, dissolving the composite polyglutamic acid in deionized water, adjusting the temperature to 50°C, stirring at 400 rpm for 60 min; then adding a polyethyleneimine solution having a mass percentage concentration of 7%, and continuing to stir at 400 rpm for 30 min to form a mixed system; S2.3, the temperature of the mixed system was raised to 70 ° C, and a 1.2% mass percentage concentration of azobisisobutyronitrile solution was added dropwise at a rate of 2 mL / min; after the addition was completed, the reaction was continued at a speed of 400 rpm stirring for 4h; S2.4, adding 0.7% hydroxyethyl cellulose solution by mass percentage to the mixed system in S1.3, and continuing to stir at a speed of 500 rpm for 2 hours; then adding hydroquinone monomethyl ether and dodecyl mercaptan, and stirring at a speed of 300 rpm for 45 minutes; S2.5. After the reaction is completed, the reaction product is naturally cooled to room temperature and filtered to obtain a salt-resistant drag reducer for oil field fracturing.
[0024] Wherein, the preparation method of composite polyglutamic acid is as follows: S1.1. Weigh the following raw materials in parts by weight respectively: 75 parts by weight of polyglutamic acid, 15 parts by weight of 1-benzyl-3-methyltriazolium chloride, 35 parts by weight of methacrylic acid, 1.5 parts by weight of potassium persulfate, 15 parts by weight of N,N-dimethylformamide, and 15 parts by weight of ethanol; S1.2, adjusting the pH value of the polyglutamic acid solution with a mass percentage concentration of 10% to 9 with 0.5 mol / L sodium hydroxide, stirring at a speed of 600 rpm for 30 min; placing the polyglutamic acid solution in a constant temperature water bath, controlling the temperature at 50°C, and stirring for 60 min; S1.3, dissolving 1-benzyl-3-methyltriazolium chloride in N,N-dimethylformamide, and adding the solution to the polyglutamic acid at a rate of 2 mL / min. After the addition is completed, stirring at a rate of 500 rpm for 4 hours to form a polyglutamic acid intermediate with a triazolium salt structure; S1.4. Raise the reaction temperature of the triazolium salt structure polyglutamic acid intermediate to 70°C, and add methacrylic acid at a rate of 2 mL / min; after the addition is completed, add a potassium persulfate solution with a mass percentage concentration of 1.5%, and stir the reaction at 70°C at a speed of 400 rpm for 10 hours; S1.5. After the reaction is completed, the reaction solution is placed in ice water for cooling to terminate the reaction; ethanol is added to the reaction solution, and the precipitate is collected by filtration; the precipitate is washed with ethanol for 5 times to remove unreacted raw materials, by-products and impurities; the precipitate is dried at a drying temperature of 60°C and a drying time of 48 hours to obtain composite polyglutamic acid.
[0025] Embodiment 2: A salt-resistant drag reducer for oilfield fracturing, comprising the following steps: S2.1. Weigh the following raw materials in parts by weight respectively: 60 parts by weight of composite polyglutamic acid, 6 parts by weight of polyethyleneimine, 1.2 parts by weight of azobisisobutyronitrile, 3 parts by weight of hydroxyethyl cellulose, 0.3 parts by weight of hydroquinone monomethyl ether, and 1.2 parts by weight of dodecyl mercaptan; S2.2, dissolving the composite polyglutamic acid in deionized water, adjusting the temperature to 50°C, stirring at 400 rpm for 60 min; then adding a polyethyleneimine solution having a mass percentage concentration of 7%, and continuing to stir at 400 rpm for 30 min to form a mixed system; S2.3, the temperature of the mixed system was raised to 70 ° C, and a 1.2% mass percentage concentration of azobisisobutyronitrile solution was added dropwise at a rate of 2 mL / min; after the addition was completed, the reaction was continued at a speed of 400 rpm stirring for 4h; S2.4, adding 0.7% hydroxyethyl cellulose solution by mass percentage to the mixed system in S1.3, and continuing to stir at a speed of 500 rpm for 2 hours; then adding hydroquinone monomethyl ether and dodecyl mercaptan, and stirring at a speed of 300 rpm for 45 minutes; S2.5. After the reaction is completed, the reaction product is naturally cooled to room temperature and filtered to obtain a salt-resistant drag reducer for oil field fracturing.
[0026] Wherein, the preparation method of composite polyglutamic acid is as follows: S1.1. Weigh the following raw materials in parts by weight respectively: 75 parts by weight of polyglutamic acid, 19 parts by weight of 1-benzyl-3-methyltriazolium chloride, 35 parts by weight of methacrylic acid, 1.5 parts by weight of potassium persulfate, 15 parts by weight of N,N-dimethylformamide, and 15 parts by weight of ethanol; S1.2, adjusting the pH value of the polyglutamic acid solution with a mass percentage concentration of 10% to 9 with 0.5 mol / L sodium hydroxide, stirring at a speed of 600 rpm for 30 min; placing the polyglutamic acid solution in a constant temperature water bath, controlling the temperature at 50°C, and stirring for 60 min; S1.3, dissolving 1-benzyl-3-methyltriazolium chloride in N,N-dimethylformamide, and adding the solution to the polyglutamic acid at a rate of 2 mL / min. After the addition is completed, stirring at a rate of 500 rpm for 4 hours to form a polyglutamic acid intermediate with a triazolium salt structure; S1.4. Raise the reaction temperature of the triazolium salt structure polyglutamic acid intermediate to 70°C, and add methacrylic acid at a rate of 2 mL / min; after the addition is completed, add a potassium persulfate solution with a mass percentage concentration of 1.5%, and stir the reaction at 70°C at a speed of 400 rpm for 10 hours; S1.5. After the reaction is completed, the reaction solution is placed in ice water for cooling to terminate the reaction; ethanol is added to the reaction solution, and the precipitate is collected by filtration; the precipitate is washed with ethanol for 5 times to remove unreacted raw materials, by-products and impurities; the precipitate is dried at a drying temperature of 60°C and a drying time of 48 hours to obtain composite polyglutamic acid.
[0027] Embodiment 3: A salt-resistant drag reducer for oilfield fracturing, comprising the following steps: S2.1. Weigh the following raw materials in parts by weight respectively: 60 parts by weight of composite polyglutamic acid, 6 parts by weight of polyethyleneimine, 1.2 parts by weight of azobisisobutyronitrile, 3 parts by weight of hydroxyethyl cellulose, 0.3 parts by weight of hydroquinone monomethyl ether, and 1.2 parts by weight of dodecyl mercaptan; S2.2, dissolving the composite polyglutamic acid in deionized water, adjusting the temperature to 50°C, stirring at 400 rpm for 60 min; then adding a polyethyleneimine solution having a mass percentage concentration of 7%, and continuing to stir at 400 rpm for 30 min to form a mixed system; S2.3, the temperature of the mixed system was raised to 70 ° C, and a 1.2% mass percentage concentration of azobisisobutyronitrile solution was added dropwise at a rate of 2 mL / min; after the addition was completed, the reaction was continued at a speed of 400 rpm stirring for 4h; S2.4, adding 0.7% hydroxyethyl cellulose solution by mass percentage to the mixed system in S1.3, and continuing to stir at a speed of 500 rpm for 2 hours; then adding hydroquinone monomethyl ether and dodecyl mercaptan, and stirring at a speed of 300 rpm for 45 minutes; S2.5. After the reaction is completed, the reaction product is naturally cooled to room temperature and filtered to obtain a salt-resistant drag reducer for oil field fracturing.
[0028] Wherein, the preparation method of composite polyglutamic acid is as follows: S1.1. Weigh the following raw materials in parts by weight respectively: 75 parts by weight of polyglutamic acid, 23 parts by weight of 1-benzyl-3-methyltriazolium chloride, 35 parts by weight of methacrylic acid, 1.5 parts by weight of potassium persulfate, 15 parts by weight of N,N-dimethylformamide, and 15 parts by weight of ethanol; S1.2, adjusting the pH value of the polyglutamic acid solution with a mass percentage concentration of 10% to 9 with 0.5 mol / L sodium hydroxide, stirring at a speed of 600 rpm for 30 min; placing the polyglutamic acid solution in a constant temperature water bath, controlling the temperature at 50°C, and stirring for 60 min; S1.3, dissolving 1-benzyl-3-methyltriazolium chloride in N,N-dimethylformamide, and adding the solution to the polyglutamic acid at a rate of 2 mL / min. After the addition is completed, stirring at a rate of 500 rpm for 4 hours to form a polyglutamic acid intermediate with a triazolium salt structure; S1.4. Raise the reaction temperature of the triazolium salt structure polyglutamic acid intermediate to 70°C, and add methacrylic acid at a rate of 2 mL / min; after the addition is completed, add a potassium persulfate solution with a mass percentage concentration of 1.5%, and stir the reaction at 70°C at a speed of 400 rpm for 10 hours; S1.5. After the reaction is completed, the reaction solution is placed in ice water for cooling to terminate the reaction; ethanol is added to the reaction solution, and the precipitate is collected by filtration; the precipitate is washed with ethanol for 5 times to remove unreacted raw materials, by-products and impurities; the precipitate is dried at a drying temperature of 60°C and a drying time of 48 hours to obtain composite polyglutamic acid.
[0029] Embodiment 4: A salt-resistant drag reducer for oilfield fracturing, comprising the following steps: S2.1. Weigh the following raw materials in parts by weight respectively: 60 parts by weight of composite polyglutamic acid, 6 parts by weight of polyethyleneimine, 1.2 parts by weight of azobisisobutyronitrile, 3 parts by weight of hydroxyethyl cellulose, 0.3 parts by weight of hydroquinone monomethyl ether, and 1.2 parts by weight of dodecyl mercaptan; S2.2, dissolving the composite polyglutamic acid in deionized water, adjusting the temperature to 50°C, stirring at 400 rpm for 60 min; then adding a polyethyleneimine solution having a mass percentage concentration of 7%, and continuing to stir at 400 rpm for 30 min to form a mixed system; S2.3, the temperature of the mixed system was raised to 70 ° C, and a 1.2% mass percentage concentration of azobisisobutyronitrile solution was added dropwise at a rate of 2 mL / min; after the addition was completed, the reaction was continued at a speed of 400 rpm stirring for 4h; S2.4, adding 0.7% hydroxyethyl cellulose solution by mass percentage to the mixed system in S1.3, and continuing to stir at a speed of 500 rpm for 2 hours; then adding hydroquinone monomethyl ether and dodecyl mercaptan, and stirring at a speed of 300 rpm for 45 minutes; S2.5. After the reaction is completed, the reaction product is naturally cooled to room temperature and filtered to obtain a salt-resistant drag reducer for oil field fracturing.
[0030] Wherein, the preparation method of composite polyglutamic acid is as follows: S1.1. Weigh the following raw materials in parts by weight respectively: 75 parts by weight of polyglutamic acid, 30 parts by weight of 1-benzyl-3-methyltriazolium chloride, 35 parts by weight of methacrylic acid, 1.5 parts by weight of potassium persulfate, 15 parts by weight of N,N-dimethylformamide, and 15 parts by weight of ethanol; S1.2, adjusting the pH value of the polyglutamic acid solution with a mass percentage concentration of 10% to 9 with 0.5 mol / L sodium hydroxide, stirring at a speed of 600 rpm for 30 min; placing the polyglutamic acid solution in a constant temperature water bath, controlling the temperature at 50°C, and stirring for 60 min; S1.3, dissolving 1-benzyl-3-methyltriazolium chloride in N,N-dimethylformamide, and adding the solution to the polyglutamic acid at a rate of 2 mL / min. After the addition is completed, stirring at a rate of 500 rpm for 4 hours to form a polyglutamic acid intermediate with a triazolium salt structure; S1.4. Raise the reaction temperature of the triazolium salt structure polyglutamic acid intermediate to 70°C, and add methacrylic acid at a rate of 2 mL / min; after the addition is completed, add a potassium persulfate solution with a mass percentage concentration of 1.5%, and stir the reaction at 70°C at a speed of 400 rpm for 10 hours; S1.5. After the reaction is completed, the reaction solution is placed in ice water for cooling to terminate the reaction; ethanol is added to the reaction solution, and the precipitate is collected by filtration; the precipitate is washed with ethanol for 5 times to remove unreacted raw materials, by-products and impurities; the precipitate is dried at a drying temperature of 60°C and a drying time of 48 hours to obtain composite polyglutamic acid.
[0031] Embodiment 5: A salt-resistant drag reducer for oilfield fracturing, comprising the following steps: S2.1. Weigh the following raw materials in parts by weight respectively: 50 parts by weight of composite polyglutamic acid, 3 parts by weight of polyethyleneimine, 0.5 parts by weight of azobisisobutyronitrile, 1 part by weight of hydroxyethyl cellulose, 0.1 parts by weight of hydroquinone monomethyl ether, and 0.5 parts by weight of dodecyl mercaptan; S2.2, dissolving the composite polyglutamic acid in deionized water, adjusting the temperature to 50°C, stirring at 400 rpm for 60 min; then adding a polyethyleneimine solution having a mass percentage concentration of 7%, and continuing to stir at 400 rpm for 30 min to form a mixed system; S2.3, the temperature of the mixed system was raised to 70 ° C, and a 1.2% mass percentage concentration of azobisisobutyronitrile solution was added dropwise at a rate of 2 mL / min; after the addition was completed, the reaction was continued at a speed of 400 rpm stirring for 4h; S2.4, adding 0.7% hydroxyethyl cellulose solution by mass percentage to the mixed system in S1.3, and continuing to stir at a speed of 500 rpm for 2 hours; then adding hydroquinone monomethyl ether and dodecyl mercaptan, and stirring at a speed of 300 rpm for 45 minutes; S2.5. After the reaction is completed, the reaction product is naturally cooled to room temperature and filtered to obtain a salt-resistant drag reducer for oil field fracturing.
[0032] Wherein, the preparation method of composite polyglutamic acid is as follows: S1.1. Weigh the following raw materials in parts by weight respectively: 75 parts by weight of polyglutamic acid, 23 parts by weight of 1-benzyl-3-methyltriazolium chloride, 20 parts by weight of methacrylic acid, 0.5 parts by weight of potassium persulfate, 10 parts by weight of N,N-dimethylformamide, and 10 parts by weight of ethanol; S1.2, adjusting the pH value of the polyglutamic acid solution with a mass percentage concentration of 10% to 9 with 0.5 mol / L sodium hydroxide, stirring at a speed of 600 rpm for 30 min; placing the polyglutamic acid solution in a constant temperature water bath, controlling the temperature at 50°C, and stirring for 60 min; S1.3, dissolving 1-benzyl-3-methyltriazolium chloride in N,N-dimethylformamide, and adding the solution to the polyglutamic acid at a rate of 2 mL / min. After the addition is completed, stirring at a rate of 500 rpm for 4 hours to form a polyglutamic acid intermediate with a triazolium salt structure; S1.4. Raise the reaction temperature of the triazolium salt structure polyglutamic acid intermediate to 70°C, and add methacrylic acid at a rate of 2 mL / min; after the addition is completed, add a potassium persulfate solution with a mass percentage concentration of 1.5%, and stir the reaction at 70°C at a speed of 400 rpm for 10 hours; S1.5. After the reaction is completed, the reaction solution is placed in ice water for cooling to terminate the reaction; ethanol is added to the reaction solution, and the precipitate is collected by filtration; the precipitate is washed with ethanol for 5 times to remove unreacted raw materials, by-products and impurities; the precipitate is dried at a drying temperature of 60°C and a drying time of 48 hours to obtain composite polyglutamic acid.
[0033] Embodiment 6: A salt-resistant drag reducer for oilfield fracturing, comprising the following steps: S2.1. Weigh the following raw materials in parts by weight respectively: 60 parts by weight of composite polyglutamic acid, 3 parts by weight of polyethyleneimine, 0.5 parts by weight of azobisisobutyronitrile, 1 part by weight of hydroxyethyl cellulose, 0.1 parts by weight of hydroquinone monomethyl ether, and 0.5 parts by weight of dodecyl mercaptan; S2.2, dissolving the composite polyglutamic acid in deionized water, adjusting the temperature to 50°C, stirring at 400 rpm for 60 min; then adding a polyethyleneimine solution having a mass percentage concentration of 7%, and continuing to stir at 400 rpm for 30 min to form a mixed system; S2.3, the temperature of the mixed system was raised to 70 ° C, and a 1.2% mass percentage concentration of azobisisobutyronitrile solution was added dropwise at a rate of 2 mL / min; after the addition was completed, the reaction was continued at a speed of 400 rpm stirring for 4h; S2.4, adding 0.7% hydroxyethyl cellulose solution by mass percentage to the mixed system in S1.3, and continuing to stir at a speed of 500 rpm for 2 hours; then adding hydroquinone monomethyl ether and dodecyl mercaptan, and stirring at a speed of 300 rpm for 45 minutes; S2.5. After the reaction is completed, the reaction product is naturally cooled to room temperature and filtered to obtain a salt-resistant drag reducer for oil field fracturing.
[0034] Wherein, the preparation method of composite polyglutamic acid is as follows: S1.1. Weigh the following raw materials in parts by weight respectively: 75 parts by weight of polyglutamic acid, 23 parts by weight of 1-benzyl-3-methyltriazolium chloride, 20 parts by weight of methacrylic acid, 0.5 parts by weight of potassium persulfate, 10 parts by weight of N,N-dimethylformamide, and 10 parts by weight of ethanol; S1.2, adjusting the pH value of the polyglutamic acid solution with a mass percentage concentration of 10% to 9 with 0.5 mol / L sodium hydroxide, stirring at a speed of 600 rpm for 30 min; placing the polyglutamic acid solution in a constant temperature water bath, controlling the temperature at 50°C, and stirring for 60 min; S1.3, dissolving 1-benzyl-3-methyltriazolium chloride in N,N-dimethylformamide, and adding the solution to the polyglutamic acid at a rate of 2 mL / min. After the addition is completed, stirring at a rate of 500 rpm for 4 hours to form a polyglutamic acid intermediate with a triazolium salt structure; S1.4. Raise the reaction temperature of the triazolium salt structure polyglutamic acid intermediate to 70°C, and add methacrylic acid at a rate of 2 mL / min; after the addition is completed, add a potassium persulfate solution with a mass percentage concentration of 1.5%, and stir the reaction at 70°C at a speed of 400 rpm for 10 hours; S1.5. After the reaction is completed, the reaction solution is placed in ice water for cooling to terminate the reaction; ethanol is added to the reaction solution, and the precipitate is collected by filtration; the precipitate is washed with ethanol for 5 times to remove unreacted raw materials, by-products and impurities; the precipitate is dried at a drying temperature of 60°C and a drying time of 48 hours to obtain composite polyglutamic acid.
[0035] Embodiment 7: A salt-resistant drag reducer for oilfield fracturing, comprising the following steps: S2.1. Weigh the following raw materials in parts by weight respectively: 70 parts by weight of composite polyglutamic acid, 3 parts by weight of polyethyleneimine, 0.5 parts by weight of azobisisobutyronitrile, 1 part by weight of hydroxyethyl cellulose, 0.1 parts by weight of hydroquinone monomethyl ether, and 0.5 parts by weight of dodecyl mercaptan; S2.2, dissolving the composite polyglutamic acid in deionized water, adjusting the temperature to 50°C, stirring at 400 rpm for 60 min; then adding a polyethyleneimine solution having a mass percentage concentration of 7%, and continuing to stir at 400 rpm for 30 min to form a mixed system; S2.3, the temperature of the mixed system was raised to 70 ° C, and a 1.2% mass percentage concentration of azobisisobutyronitrile solution was added dropwise at a rate of 2 mL / min; after the addition was completed, the reaction was continued at a speed of 400 rpm stirring for 4h; S2.4, adding 0.7% hydroxyethyl cellulose solution by mass percentage to the mixed system in S1.3, and continuing to stir at a speed of 500 rpm for 2 hours; then adding hydroquinone monomethyl ether and dodecyl mercaptan, and stirring at a speed of 300 rpm for 45 minutes; S2.5. After the reaction is completed, the reaction product is naturally cooled to room temperature and filtered to obtain a salt-resistant drag reducer for oil field fracturing.
[0036] Wherein, the preparation method of composite polyglutamic acid is as follows: S1.1. Weigh the following raw materials in parts by weight respectively: 75 parts by weight of polyglutamic acid, 23 parts by weight of 1-benzyl-3-methyltriazolium chloride, 20 parts by weight of methacrylic acid, 0.5 parts by weight of potassium persulfate, 10 parts by weight of N,N-dimethylformamide, and 10 parts by weight of ethanol; S1.2, adjusting the pH value of the polyglutamic acid solution with a mass percentage concentration of 10% to 9 with 0.5 mol / L sodium hydroxide, stirring at a speed of 600 rpm for 30 min; placing the polyglutamic acid solution in a constant temperature water bath, controlling the temperature at 50°C, and stirring for 60 min; S1.3, dissolving 1-benzyl-3-methyltriazolium chloride in N,N-dimethylformamide, and adding the solution to the polyglutamic acid at a rate of 2 mL / min. After the addition is completed, stirring at a rate of 500 rpm for 4 hours to form a polyglutamic acid intermediate with a triazolium salt structure; S1.4. Raise the reaction temperature of the triazolium salt structure polyglutamic acid intermediate to 70°C, and add methacrylic acid at a rate of 2 mL / min; after the addition is completed, add a potassium persulfate solution with a mass percentage concentration of 1.5%, and stir the reaction at 70°C at a speed of 400 rpm for 10 hours; S1.5. After the reaction is completed, the reaction solution is placed in ice water for cooling to terminate the reaction; ethanol is added to the reaction solution, and the precipitate is collected by filtration; the precipitate is washed with ethanol for 5 times to remove unreacted raw materials, by-products and impurities; the precipitate is dried at a drying temperature of 60°C and a drying time of 48 hours to obtain composite polyglutamic acid.
[0037] Comparative Example 1 The method of Example 3 was adopted, but composite polyglutamic acid was not used. Polyglutamic acid was directly used to prepare the salt-resistant drag reducer for oilfield fracturing.
[0038] Comparative Example 2 The method of Example 3 is adopted to remove methacrylic acid in the preparation method of composite polyglutamic acid.
[0039] The present invention is a salt-resistant drag reducer for oilfield fracturing prepared by composite polyglutamic acid, wherein the performance index inspection items and inspection standards of the salt-resistant drag reducer are as follows: According to the SY / T 5677-2016 standard, NaCl aqueous solutions with concentrations of 5000ppm, 10000ppm, 20000ppm and 50000ppm were prepared, and the salt-resistant drag reducer was added to the above solutions with different mineralization degrees according to the recommended proportion, and stirred thoroughly to ensure complete dissolution; under the same conditions (such as temperature, shear rate, etc.), the apparent viscosity was measured using a rotational viscometer, and the apparent viscosity retention rate was calculated to evaluate the salt resistance of the salt-resistant drag reducer; a higher apparent viscosity retention rate indicates that the drag reducer can better maintain its molecular structure and morphology in a high-salt environment, and resist the compression and destructive effects of salt ions on the molecular chains.
[0040] According to the SY / T 5677-2016 standard, a pipeline flow test device is used to simulate the flow conditions in the actual formation. Usually, an annular tube or a straight tube is used as the test pipe, and the inner diameter is generally 25-50mm. A certain concentration of salt-resistant drag reducer solution is prepared as needed, and a control sample without drag reducer is prepared. The drag reduction rate is calculated by the formula at the set temperature and shear rate; the higher the drag reduction rate, the greater the reduction in resistance encountered by the fracturing fluid when flowing in the pipeline, so that during the fracturing construction process, too high a pumping pressure is not required to push the fracturing fluid forward.
[0041] The salt-resistant drag reducers prepared in Examples 1-7 and Comparative Examples 1-2 were tested according to the above standards, and the obtained data are shown in Table 1: Table 1 Performance data of salt-resistant drag reducers of Examples 1-7 and Comparative Examples 1-2 It can be seen from Examples 1-4 that: when the mass ratio of 1-benzyl-3-methyltriazolium chloride to polyglutamic acid in the composite polyglutamic acid gradually increases, the drag reduction rate and apparent viscosity retention rate of the salt-resistant drag reducer gradually increase, but when the mass ratio of 1-benzyl-3-methyltriazolium chloride to polyglutamic acid reaches a certain value, the drag reduction rate and apparent viscosity retention rate of the salt-resistant drag reducer gradually decrease. It can be seen that with the increase of the mass ratio of 1-benzyl-3-methyltriazolium chloride, the drag reduction rate and apparent viscosity retention rate of the salt-resistant drag reducer are improved, but excessive increase may reduce the drag reduction rate and apparent viscosity retention rate of the salt-resistant drag reducer; The addition of 1-benzyl-3-methyltriazolium chloride may increase the flexibility of polyglutamic acid molecular chains through specific interactions such as ionic bonds, hydrogen bonds or van der Waals forces. This effect makes the molecular chains easier to stretch and orient in the solution, thereby reducing the friction between internal molecules and improving the drag reduction rate. At the same time, this flexibility also helps to maintain a high apparent viscosity. With the increase of mass ratio, 1-benzyl-3-methyltriazolium chloride may form a more complete intermolecular network structure with polyglutamic acid. This network structure can prevent the aggregation and entanglement of molecular chains and make the molecular distribution in the solution more uniform. Under the action of external force, the molecular chains can move in a more orderly manner, thereby further improving the drag reduction rate and apparent viscosity retention rate.
[0042] The ionic groups in 1-benzyl-3-methyltriazolium chloride can interact with salt ions in the solution and play a certain ion shielding effect; as its content increases, it can more effectively shield the influence of salt ions on the polyglutamic acid molecular chain, preventing the molecular chain from shrinking or aggregating due to the action of salt ions, which not only improves the apparent viscosity retention rate, but also maintains good drag reduction performance; in addition, the addition of this compound can adjust the charge density of the composite polyglutamic acid, and the appropriate charge density helps the molecular chain maintain good solubility and dispersibility in the salt solution, avoiding the performance degradation due to salting out and other effects; therefore, under different salt concentrations, the salt-resistant drag reducer can maintain a high drag reduction rate and apparent viscosity retention rate.
[0043] Furthermore, by comparing Examples 5-7, it can be seen that: when other components remain unchanged, only when the proportion of composite polyglutamic acid gradually increases, the drag reduction rate and apparent viscosity retention rate of the salt-resistant drag reducer gradually increase. It can be seen that polyglutamic acid has a special polymer structure, and its molecular chain is rich in a large number of active groups such as carboxyl groups. These groups can interact with water molecules and other substances through hydrogen bonds, electrostatic effects, etc.; as the proportion of composite polyglutamic acid increases, more active groups participate in the system, which helps to form a more stable solution structure, thereby improving the apparent viscosity retention rate; in addition, the special molecular chain morphology and flexibility of polyglutamic acid can be in the fluid It reduces internal friction resistance during flow, thereby improving the drag reduction rate; polyglutamic acid has good water solubility and dispersibility, and can be evenly dispersed in the solution. As its proportion increases, other components can be better dispersed evenly in the system, making the entire salt-resistant drag reducer system more stable and uniform, which reduces the increase in resistance and viscosity decrease caused by local concentration unevenness, and is beneficial to improving the drag reduction rate and apparent viscosity retention rate; at the same time, groups such as carboxyl in polyglutamic acid can undergo complexation with salt ions in the solution. As its proportion increases, it can more effectively bind to salt ions in the solution, reduce the influence of salt ions on the viscosity of the system, and improve the apparent viscosity retention rate.
[0044] Comparing Example 3 with Comparative Example 1, it can be seen that when polyglutamic acid is directly used to prepare the salt-resistant drag reducer for oilfield fracturing without using composite polyglutamic acid, the drag reduction rate and apparent viscosity retention rate of the salt-resistant drag reducer are significantly reduced.
[0045] Taking Example 3 as the best example and combining it with Comparative Example 2, it can be seen that in the preparation method of composite polyglutamic acid, when methacrylic acid is removed, the drag reduction rate and apparent viscosity retention rate of the salt-resistant drag reducer are significantly reduced; The hydrophilic groups (such as carboxyl) and specific chemical structure in methacrylic acid enable it to form a stable hydration layer with water molecules, thereby preventing aggregation and precipitation between the molecular chains of composite polyglutamic acid. Studies have shown that the introduction of methacrylic acid can increase the extension of the molecular chain, while the hydrophobic groups are more likely to associate with the network, thereby improving the dispersibility and stability. However, when methacrylic acid is removed, the dispersion stability of the solution will decrease significantly, and agglomeration will easily occur, resulting in a decrease in the drag reduction rate and apparent viscosity retention rate. The carboxyl and other groups in methacrylic acid can interact with the salt ions in the solution, reducing the influence of the salt ions on the polyglutamic acid molecular chains, thereby preventing the molecular chains from shrinking or agglomerating due to salting out and other effects. In addition, the presence of methacrylic acid can optimize the charge distribution of the composite polyglutamic acid molecules, so that they have a suitable charge state in the salt solution, thereby maintaining the solubility and stability of the molecules. However, after the removal of methacrylic acid, this ion shielding effect is weakened, and the salt ions are more likely to destroy the molecular chain structure and solution stability, resulting in a decrease in the performance of the salt-resistant drag reducer.
[0046] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A salt-resistant drag reducer for oilfield fracturing, characterized in that: The method comprises the following raw materials: 50-70 parts by weight of composite polyglutamic acid, 3-10 parts by weight of polyethyleneimine, 0.5-2 parts by weight of azobisisobutyronitrile, 1-5 parts by weight of hydroxyethyl cellulose, 0.1-0.5 parts by weight of hydroquinone monomethyl ether, and 0.5-2 parts by weight of dodecyl mercaptan; The composite polyglutamic acid is prepared by grafting and copolymerizing polyglutamic acid with 1-benzyl-3-methyltriazolium chloride and adding methacrylic acid.
2. The salt-resistant drag reducer for oilfield fracturing according to claim 1, characterized in that: The preparation method of the composite polyglutamic acid is as follows: S1.
1. Weigh the following raw materials in parts by weight respectively: 60-90 parts by weight of polyglutamic acid, 10-30 parts by weight of 1-benzyl-3-methyltriazolium chloride, 20-50 parts by weight of methacrylic acid, 0.5-2 parts by weight of potassium persulfate, 10-20 parts by weight of N,N-dimethylformamide, and 10-20 parts by weight of ethanol; S1.2, adjust the pH value of the polyglutamic acid solution to 8-10 with 0.1-1 mol / L sodium hydroxide, and stir at 300-600 rpm for 15-30 min; place the polyglutamic acid solution in a constant temperature water bath, control the temperature at 40-50°C, and stir for 30-60 min; S1.3, dissolving 1-benzyl-3-methyltriazolium chloride in N,N-dimethylformamide, and adding dropwise to the polyglutamic acid solution. After the addition is completed, stirring at a speed of 400-600 rpm for 2-4 hours to form a polyglutamic acid intermediate with a triazolium salt structure; S1.4, raising the reaction temperature of the polyglutamic acid intermediate with a triazolium salt structure to 60-70°C, and adding methacrylic acid dropwise at a rate of 0.5-2 mL / min; after the addition is completed, adding potassium persulfate solution, and stirring the reaction at 60-70°C at a speed of 400-600 rpm for 6-10 hours; S1.
5. After the reaction is completed, the reaction solution is placed in ice water to cool and terminate the reaction; ethanol is added to the reaction solution, and the precipitate is collected by filtration; the precipitate is washed with ethanol for 3-5 times to remove unreacted raw materials, by-products and impurities; the precipitate is dried to obtain composite polyglutamic acid.
3. The salt-resistant drag reducer for oilfield fracturing according to claim 2, characterized in that: In S1.2, the polyglutamic acid solution is prepared by dissolving polyglutamic acid in deionized water to obtain a polyglutamic acid solution having a mass percent concentration of 5-15%.
4. The salt-resistant drag reducer for oilfield fracturing according to claim 2, characterized in that: In S1.3, the rate of adding 1-benzyl-3-methyltriazolium chloride is 0.5-2 mL / min.
5. The salt-resistant drag reducer for oilfield fracturing according to claim 2, characterized in that: In S1.4, the mass percentage concentration of the potassium persulfate solution is 0.5-2%.
6. The salt-resistant drag reducer for oilfield fracturing according to claim 2, characterized in that: In the above S1.5, the drying temperature is 40-60°C and the drying time is 24-48h.
7. The salt-resistant drag reducer for oilfield fracturing according to claim 1, characterized in that: The preparation method of the salt-resistant drag reducer is as follows: S2.
1. Weigh the following raw materials in parts by weight respectively: 50-70 parts by weight of composite polyglutamic acid, 3-10 parts by weight of polyethyleneimine, 0.5-2 parts by weight of azobisisobutyronitrile, 1-5 parts by weight of hydroxyethyl cellulose, 0.1-0.5 parts by weight of hydroquinone monomethyl ether, and 0.5-2 parts by weight of dodecyl mercaptan; S2.2, dissolve the composite polyglutamic acid in deionized water, adjust the temperature to 40-50°C, and stir at 300-400rpm for 30-60min; then add the polyethyleneimine solution, and continue stirring at 300-400rpm for 15-30min to form a mixed system; S2.3, the temperature of the mixed system was raised to 60-70 ℃, azobisisobutyronitrile solution was added dropwise; after the addition was completed, the reaction was continued at a speed of 300-400rpm stirring for 2-4h; S2.4, adding the hydroxyethyl cellulose solution to the mixed system in S1.3, continuing to stir at a speed of 400-500 rpm for 1-2 hours; then adding hydroquinone monomethyl ether and dodecyl mercaptan, stirring at a speed of 200-300 rpm for 15-45 minutes; S2.
5. After the reaction is completed, the reaction product is naturally cooled to room temperature and filtered to obtain a salt-resistant drag reducer for oil field fracturing.
8. The salt-resistant drag reducer for oilfield fracturing according to claim 7, characterized in that: In S2.2, the polyethyleneimine solution is prepared by dissolving polyethyleneimine in deionized water to obtain a polyethyleneimine solution having a mass percent concentration of 5-10%.
9. The salt-resistant drag reducer for oilfield fracturing according to claim 7, characterized in that: In S2.3, the azobisisobutyronitrile solution is prepared by dissolving azobisisobutyronitrile in anhydrous ethanol to obtain an azobisisobutyronitrile solution having a mass percentage concentration of 0.1-2%, and the dripping speed is 0.5-2 mL / min.
10. The salt-resistant drag reducer for oilfield fracturing according to claim 7, characterized in that: In S2.4, the hydroxyethyl cellulose solution is prepared by dissolving hydroxyethyl cellulose in deionized water to obtain a hydroxyethyl cellulose solution having a mass percent concentration of 0.5-1%.
Citation Information
Patent Citations
Water base fracture drag reducer
CN103265940A
Drag reducer for fracturing fluid and preparation method thereof
CN104232056A
Mercapto-triazole gas pipeline drag reducer and preparation method thereof
CN104629359A
Production method of salt-resistant drag reducer for oil well fracturing
CN118755467A
Environment-friendly drag reducer for fracturing and preparation method thereof
CN118792040A